2014
DOI: 10.1002/biot.201400555
|View full text |Cite
|
Sign up to set email alerts
|

Biologically synthesized silver nanoparticles induce neuronal differentiation of SH‐SY5Y cells via modulation of reactive oxygen species, phosphatases, and kinase signaling pathways

Abstract: Nano-scale materials are noted for unique properties, distinct from those of their bulk material equivalents. In this study, we prepared spherical silver nanoparticles (AgNPs) with an average size of about 30 nm and tested their potency to induce neuronal differentiation of SH-SY5Y cells. Human neuroblastoma SH-SY5Y cells are considered an ideal in vitro model for studying neurogenesis, as they can be maintained in an undifferentiated state or be induced to differentiate into neuron-like phenotypes in vitro by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…After incubation for 48 h, the medium was exchanged with a fresh medium containing EZ-Cytox (Daeil Lab Service, Seoul, Korea) and incubated for an additional 3–4 h at 37 °C in an atmosphere of 5% CO 2 . The absorbance was measured at 450 nm by using a microplate reader Bio-Rad x-Mark TM spectrophotometer (Bio-Rad, Philadelphia, PA, USA) and the cell viability was calculated by comparing the viability of treated cells with that of non-treated cells, as previously described [75]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation for 48 h, the medium was exchanged with a fresh medium containing EZ-Cytox (Daeil Lab Service, Seoul, Korea) and incubated for an additional 3–4 h at 37 °C in an atmosphere of 5% CO 2 . The absorbance was measured at 450 nm by using a microplate reader Bio-Rad x-Mark TM spectrophotometer (Bio-Rad, Philadelphia, PA, USA) and the cell viability was calculated by comparing the viability of treated cells with that of non-treated cells, as previously described [75]. …”
Section: Methodsmentioning
confidence: 99%
“…The indicated cells were then pre-incubated with the ROS scavenger, NAC (1 mM). After a 1-h pre-incubation period, the cells were treated with VPA, DOX, and the VPA and DOX combination for 48 h. Intracellular ROS levels were then analyzed using the fluorescent probe H 2 DCFDA [75]. Briefly, 10 μM H 2 DCFDA was added to the cells, which were incubated for 30 min at 37 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Dayem et al [26] observed that cells treated with AgNPs had significantly altered cell morphology and neurite length caused by enhanced expression of neuronal differentiation markers such as Map-2, β-tubulin III, synaptophysin, neurogenin-1, Gap-43, and Drd-2 [26]. Similarly, another group from Israel found that substrates coated with AgNPs, serving as favorable anchoring sites, significantly enhanced neurite outgrowth [87].…”
Section: Cellular Effects Of Agnps On Neuronal Cellsmentioning
confidence: 99%
“…Recently, Xu et al [25] reported that AgNPs induced toxicity and neuronal cell death in primary rat cortical cell cultures, via modulation of cytoskeleton components, perturbations of pre- and postsynaptic proteins, and mitochondrial dysfunction. Dayem et al [26] found that AgNPs could promote neuronal differentiation of SH-SY5Y cells through increased intracellular ROS generation, enhanced activation of kinases such as protein kinase B (PKB), also known as Akt, is a serine/threonine-specific protein kinase and Erk1/2, and modulation of expression levels of dual-specificity phosphatase (DUSP) genes.…”
Section: Introductionmentioning
confidence: 99%
“…Antidermatophytic activity of AgNPs synthesized by lemon peels was also documented very recently by Nisha et al [112]. AgNPs were also found to induce neuronal differentiation by modulating intracellular signaling pathways, thus there potential could be applied for stem cell research and therapy [113]. Antimalarial application of synthesized NPs is also widely acknowledged [54,114].…”
Section: Miscellaneous Applicationsmentioning
confidence: 90%